Strategy of HR development at high-tech enterprises - Kyriy, V.; Liubicheva, O.; Moskavtsova, K. (ХНУРЕ, 2017)
The subject matter of the study is the mechanism of functioning and development of HR high-tech enterprise. In Ukraine, the most high-tech sector of the economy is represented by the information technology sector, namely the sub-sector of the development and implementation of information products and services. The relevance of researching HR processes in high-tech enterprises is due not only to the rapid growth of the IT sector of the Ukrainian market, but also to the need to study the work of the HR system taking into account the stages of the life cycle of such an enterprise. The development of a high-tech sector requires the continuous development of HR methods and tools. The goal of the work is to study the current state and directions of HR development in IT enterprises in accordance with the stages of the life cycle of such enterprises. The objectives of the work are to summarize the existing practical trends in HR and to study their structural characteristics; to improve the criterial approach to determining the relationship between the stage of the life cycle of a high-tech enterprise and the stage of development of the HR service. The general scientific and applied methods of theoretical and empirical research were used in the work: observation, comparison and analysis of empirical data, generalization, synthesis - for posing a problem, studying the laws of the development of the object of research; statistical - to assess the current state of the industry; graphic to illustrate the results of the activities of enterprises and the formulation of findings of the studies. The result of the research is the formation of the fundamentals of a criterial approach to determining the relationship between the stage of the life cycle of a high-tech enterprise and the stage of development of the HR based on the ordering of existing trends in the field of HR. It is determined that strategic direction for modern enterprises is creation of HR-business partner, which will allow to solve complex problems of modern adaptive HR management tasks. The proposed indicators of HR performance evaluation depending on the stage of HR development.
Keywords: HR high-tech enterprises; evaluation of activity HR; stages of HR development; strategy of development HR